Feasibility study on replacement of steel signboard post with prestressed concrete post - Awang, Abdullah Zawawi; Rais, Ahmad Zaidon; Abd. Hamid, Hazlan; Yassin, Mohamad Salleh (Universiti Teknologi Malaysia, 2002)
The main aim of this feasibility study was to evaluate the performance of prestressed concrete post due to replacing steel material in designing signboard posts for expressway in Malaysia. The scope of the study was mainly on mild steel with a diameter of 406 mm circular hollow section, which is the biggest size that has been used by PLUS Bhd. Some comparisons were made based on earlier studies in evaluating the performance of both materials in construction and service stages. The performance of both materials in many aspects was investigated; they were safety, strength, workability, durability and serviceability aspects. The prestressed concrete was found has a good potential to be used as a standard signboard post for expressway in Malaysia in future. It has a good performance and some advantages which are not found in steel posts. By using prestressed concrete post, a dependency of the construction industry to steel material supply can be solved and consequently the overall cost of the signboard construction can be reduced.